Polygamy in the Perspective of Tafsīr Al-Aḥkām and Islamic Law: An Examination of the Gayo Luwes Community in Aceh, Indonesia - Aziz, Nasaiy; Rispalman, Rispalman; Anggraini, Tika (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The law on marriage, adheres to the principle of monogamy, but in other parts, it is stated that under certain circumstances polygamy is justified. The main problem studied was the practice of polygamy without the permission of wives in Gayo Lues Regency, Aceh. This study employs empirical legal methodologies and applies theoretical frameworks grounded on Islamic law, specifically utilizing the approach of tafsīr al-aḥkām. The collection of data was conducted through the utilization of in-depth interviews and a comprehensive review of relevant literature. The findings of the study revealed significant variations in the occurrence of non-consensual polygamy in Pantan Weather subdistrict, Gayo Regency. Polygamy entails both bad and positive consequences, with the former outweighing the latter in terms of quantity. The adverse consequences encompass spousal inequity, the disregard for the rights of women and children, the proliferation of animosity among spouses, and the erosion of familial bonds. In contrast, the potential benefits of engaging in polygamy primarily revolve around the avoidance of immoral behavior, specifically adultery, and the facilitation of subsequent marriages. By entering into multiple marriages without the explicit consent of one's spouse, an individual may perceive certain advantages, such as the acquisition of desirable outcomes. Conversely, the fear of experiencing negative consequences, such as infidelity, may serve as a motivating factor for individuals to pursue polygamous relationships. Moreover, as posited by scholars of interpretation, both ancient and contemporary, the fundamental principle of marriage in Islamic jurisprudence is monogamy. However, if an individual engages in polygamy, it is imperative to uphold principles of justice, responsibility, and the preservation of familial harmony and tranquility. This study contributes to the understanding that polygamy may be considered as a viable option in exceptional circumstances, but only under the condition that it is practiced with fairness and equity by specific individuals.